2015
DOI: 10.1002/wrna.1296
|View full text |Cite
|
Sign up to set email alerts
|

Engineering RNA‐binding proteins with diverse activities

Abstract: With generations of efforts to understand RNA functions in diverse cellular processes, RNA-binding proteins (RBPs) have emerged to be one of the central players in regulating RNA-related pathways. RBPs control almost all aspects of RNA processing via recognizing their RNA target(s). Most of these proteins have a modular configuration, with one or more RNA-binding domain for target recognition and various functional modules to affect the metabolism and biological functions of RNA. Thus, engineering RNA-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 101 publications
(211 reference statements)
0
15
0
Order By: Relevance
“…Because of the modular recognition of RNA sequences and the simple recognition code, PUF domains have been engineered to target designed RNA sequences for various purposes (43,44). These efforts have all been based on the classic PUF domains, which contain eight repeats and bind similar sequences that bear a 5΄ UGUR (where R is a purine) motif and a 3΄ UA motif.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the modular recognition of RNA sequences and the simple recognition code, PUF domains have been engineered to target designed RNA sequences for various purposes (43,44). These efforts have all been based on the classic PUF domains, which contain eight repeats and bind similar sequences that bear a 5΄ UGUR (where R is a purine) motif and a 3΄ UA motif.…”
Section: Discussionmentioning
confidence: 99%
“…As their fascinating properties and unusual evolutionary behaviour become better understood, other potential applications of RFL proteins besides fertility restoration are coming to the fore. PPR proteins are being investigated for their potential as custom-made RNA processing tools 24 62 , and of all the natural PPR proteins, RFL proteins are perhaps the best suited for biotechnological manipulation given their recurrent selection for diversity in binding site selection.…”
Section: Discussionmentioning
confidence: 99%
“…To validate the function of these proteins, we fused the candidate RBPs to a programmable RNA binding domain (i.e., Puf domain) that can be designed to bind any 8-nt RNA sequences 38 , and co-expressed the fusion proteins with the circRNAs containing their cognate targets. We found that the specific tethering of PABPC1 and hnRNP U clearly promoted translation of the circRNA, whereas the ELAVL1 (HuR) and hnRNP A1 did not affect translation when tethered to the same site ( Fig.…”
Section: Trans-acting Factors That Bind To Ires-like Short Elements Tmentioning
confidence: 99%